2020
DOI: 10.1097/j.pain.0000000000002022
|View full text |Cite
|
Sign up to set email alerts
|

GABA and glutamate in pediatric migraine

Abstract: Supplemental Digital Content is Available in the Text. Using magnetic resonance spectroscopy in vivo, we show GABA and glutamate alterations in children aged 7 to 13 years with migraine, which are associated with migraine characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Finally, although several MRS studies on thalamic GABA levels have been conducted, and thalamic GABA levels in the controls in the current study were equivalent to those observed by Pollack, 35 the quantitative GABA values were affected by multiple factors, including field strength MRI scanner (3 T, 4 T 34 ), MRS sequence (STEAM, 36 PRESS, MEGA‐PRESS, or JEPSI 34 ), location of MRS VOI (unilateral 37 or bilateral thalamus), post‐process software (LcModel 38 or Gannet), co‐edited macromolecule signals, and internal reference (Cr or water 39 ). For example, only taking internal‐referenced thalamic GABA levels into consideration, the gap in quantitative thalamic GABA values in normal controls in different studies was over 10‐fold 37 .…”
Section: Limitationssupporting
confidence: 76%
“…Finally, although several MRS studies on thalamic GABA levels have been conducted, and thalamic GABA levels in the controls in the current study were equivalent to those observed by Pollack, 35 the quantitative GABA values were affected by multiple factors, including field strength MRI scanner (3 T, 4 T 34 ), MRS sequence (STEAM, 36 PRESS, MEGA‐PRESS, or JEPSI 34 ), location of MRS VOI (unilateral 37 or bilateral thalamus), post‐process software (LcModel 38 or Gannet), co‐edited macromolecule signals, and internal reference (Cr or water 39 ). For example, only taking internal‐referenced thalamic GABA levels into consideration, the gap in quantitative thalamic GABA values in normal controls in different studies was over 10‐fold 37 .…”
Section: Limitationssupporting
confidence: 76%
“…The elevated baseline levels of GABA+ observed in this cohort [ 24 ] and by others [ 14 , 20 , 25 ] have been proposed as a potential cause of migraine, due to being present in people with migraine but not in healthy controls. However, given the cross-sectional nature of the studies, the temporal and directional nature of these findings are unknown.…”
Section: Introductionmentioning
confidence: 51%
“…Peek et al demonstrated that improvements in migraine frequency, intensity, and disability are associated with increased GABA+ levels in the anterior cingulate cortex [ 64 ]. Bell et al found that higher glutamate levels in the thalamus and higher GABA/Glx ratios in the sensorimotor cortex were associated with longer durations of pediatric migraine [ 10 ]. Additionally, lower GABA levels in the sensorimotor cortex are associated with more frequent migraine attacks [ 10 ].…”
Section: Discussionmentioning
confidence: 99%